Human Rights and Disability Advocacy - Schulze, Marianne, 1975-; Sabatello, Maya (Book collections on Project MUSE., 2014)
This book brings together perspectives from civil society representatives who played key roles in the drafting of the Convention on the Rights of Persons with Disabilities, shedding light on the emergent practices of a "new diplomacy" and the larger enterprise of human rights advocacy at the international level.